2021
DOI: 10.1177/02692155211010279
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and experiences of older patients and healthcare professionals regarding shared decision-making in pulmonary rehabilitation: A qualitative study

Abstract: Objective: To understand the perceptions and experiences of older patients with chronic obstructive pulmonary disease (COPD) and healthcare professionals (HCPs) regarding shared decision-making in pulmonary rehabilitation (PR). Design: A qualitative study using single, semi-structured interviews, and thematic analysis. Setting: Face-to-face interviews were conducted in the Jiangnan University, in hospital and in patients’ homes. Participants: Twenty-two older patients with COPD and 29 HCPs. Methods: An initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Still, due to the personal characteristics of the older women, this task was not easy. This is consistent with other studies that describe a perception of health personnel who also classify older people as stubborn and complicated in the attempt to include them in care processes [ 72 , 73 ]. All these moments, related to situations of AL, SDM and participation in care, were plagued with anomalies that did not allow older women to take an active agency role in their care, nor did primary care nurses establish therapeutic communication with them.…”
Section: Discussionsupporting
confidence: 91%
“…Still, due to the personal characteristics of the older women, this task was not easy. This is consistent with other studies that describe a perception of health personnel who also classify older people as stubborn and complicated in the attempt to include them in care processes [ 72 , 73 ]. All these moments, related to situations of AL, SDM and participation in care, were plagued with anomalies that did not allow older women to take an active agency role in their care, nor did primary care nurses establish therapeutic communication with them.…”
Section: Discussionsupporting
confidence: 91%
“…13 Shared decision-making promotes patient involvement in clinical decision-making in partnership with health professionals. 17 Shared decision-making can be used in the development, design and implementation of healthcare interventions by creating tailored treatment programmes and patient-centred goals according to patients' preferences. 18 Rehabilitation aims to enable people to optimise their mobility, capability, autonomy, function and quality of life.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…It also relates to the connections that patients have with health professionals,16 and the degree to which patients participate in the design and delivery of health initiatives 13. Shared decision-making promotes patient involvement in clinical decision-making in partnership with health professionals 17. Shared decision-making can be used in the development, design and implementation of healthcare interventions by creating tailored treatment programmes and patient-centred goals according to patients’ preferences 18…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 Studies pointed to the need to integrate SDM into pulmonary rehabilitation services. 13 , 14 However, little research has been found on the application of SDM in pulmonary rehabilitation and no decision aids for pulmonary rehabilitation have been developed.…”
Section: Introductionmentioning
confidence: 99%